A geographical interpretation of landscape structure - Csorba, Péter (4D Journal of Landscape Architecture and Garden Art, 2014)
Landscape is one of the most important concepts of Geography, where competence of Geography cannot be argued. It is special, that definition of this principle is in permanent change, what shows the development of the discipline.
Keywords: landscape structure; landscape factor; landscape typology; landscape metrics; landscape pattern